2020
DOI: 10.15789/2220-7619-iol-1232
|View full text |Cite
|
Sign up to set email alerts
|

Lung memory T-cell response in mice following intranasal immunization with influenza vector expressing mycobacterial proteins

Abstract: Improving specific prevention of tuberculosis continues to be a top priority in phthisiology. “Prime-boost” vaccination schemes aim to maintain adequate levels of specific immunity while forming long-term protection. They are based on sequential use of BCG vaccine and new vaccine candidates expressing protective mycobacterial proteins. The development of new tuberculosis prevention approaches requires an understanding of how the anti-tuberculosis immune response forms and which mechanisms provide TB protection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…on animal models, such as mice and guinea pigs, showed the vaccine to be completely safe (Buzitskaya et al, 2022). Moreover, it was established that vaccinated animals developed a strong antigen-specific T-cell immune response and a high level of protection, one that is not inferior to that offered by a commercial Bacillus Calmette-Guérin (BCG) vaccine (Shurygina et al, 2014;Stukova et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…on animal models, such as mice and guinea pigs, showed the vaccine to be completely safe (Buzitskaya et al, 2022). Moreover, it was established that vaccinated animals developed a strong antigen-specific T-cell immune response and a high level of protection, one that is not inferior to that offered by a commercial Bacillus Calmette-Guérin (BCG) vaccine (Shurygina et al, 2014;Stukova et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Similar studies assessing the safety of recombinant influenza viruses expressing M. tuberculosis’ proteins ESAT-6 and Ag-85 in laboratory animals such as mice and guinea pigs have proved them to be completely safe. They have also demonstrated that animals immunised with recombinant influenza viruses developed a T-cell immune response and a level of protection that was not inferior to those induced by commercial BCG vaccines [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%